Mindfulness to improve the mental health of university students. A systematic review and meta-analysis - Ana María González-Martín; Ana María González-Martín; Agustín Aibar-Almazán; Yulieth Rivas-Campo; Yolanda Castellote-Caballero; María del Carmen Carcelén-Fraile (Frontiers Media S.A., 2023)
ObjectivesThis systematic review and meta-analysis was to analyze the effects of a mindfulness program on mental health in university students.MethodsA systematic review was conducted using the databases Pubmed, Scopus, Web of Science and CINAHL. The selected studies had to incorporate a mindfulness intervention in university students. The methodological quality of the collected articles was evaluated using the PEDro scale.ResultsWe initially identified 321 studies, of which 21 were included in this review. The interventions focused on mindfulness with durations ranging from 8 weeks to 3 months. The results demonstrated significant effects of a mindfulness intervention on mental health in university students.ConclusionThis systematic review and meta-analysis found that mindfulness is effective for improving the mental health of college students.Systematic Review Registrationidentifier: CRD42023441453.